Vision Mātauranga research directions: opportunities for iwi and hapū management plans - Kaiser LH; Saunders WSA (Taylor Francis Group, 2021)
The Ministry of Business, Innovation and Employment (MBIE) Vision Mātauranga policy has created a clear message for researchers in Aotearoa/New Zealand – that research conducted in Aotearoa New Zealand should recognise and support the ‘unlocking of the innovative potential of Māori for the benefit of all New Zealand’ and be designed with a clear engagement pathway. However, there is still confusion amongst many researchers on where to begin when considering the Vision Mātauranga component of their research. Iwi and hapū management plans are a valuable resource for researchers to use as a starting point when planning projects, particularly with regard to Vision Mātauranga opportunities. Many of these plans outline the issues, challenges and resource priorities that an iwi or hapū may have, as well providing historical context for their knowledge and experiences. Despite their usefulness, our research found that only 22% of natural hazard researchers surveyed used them in their research process. The purpose of this paper is to raise awareness of the value of these plans for researchers, particularly when developing a research project; and to provide a starting point for engagement opportunities and activities with Māori.
(c) 2021 The Author/s